The presence of bilateral imbalance of the lower limbs in elite youth soccer players of different ages - Atkins, S.; Bentley, I.; Hurst, H.; Sinclair, J.; Hesketh, C. (The Journal of Strength and Conditioning Research, 2016)
The aim of this study was to examine bilateral differences in ground reaction forces (GRF), measured during a deep squat (DS) exercise, in a population of elite youth soccer players. Bilateral muscle balance is a key component in promoting musculoskeletal health of performers, yet there is a limited evidence base investigating such imbalances in youth. Seventy-four subjects were assigned to performance groups according to chronological age (younger than 13, 14, 15, 16, 17 years). Analysis of physical maturity status revealed that very few players were classified as "early" or "late" maturers. Players completed an overhead DS exercise, as part of preseason functional movement screening. Peak GRF were assessed using a twin force plate system. Significant differences (p = 0.05) were identified between right and left side peak GRF for all groups except the youngest (U13) and oldest (U17). Nondominant "sides" showed the highest levels of PGRF across all groups. The magnitude of PGRF was not significantly different both within and between groups, except for the left side in the U13 to U15 groups (p = 0.04). Results from this study show that performance asymmetry is marked in adolescence. There seems a "trigger point" during the early stage of adolescence, when bilateral imbalances become marked. These differences do seem to reduce during the later stages of adolescence. Correct attention to focussed training, designed to remediate any imbalance, is warranted in adolescent groups. This is important with respect of the key associations between bilateral asymmetry and risk of injury.